All the women are white, all the Blacks are men, but some of us are brave: Black women's studies - Hull, Gloria T.; Scott, Patricia Bell; Smith, Barbara (The Feminist Press at the City University of New York, 2015)
This ground-breaking collection provides hours of enjoyment for the general reader and a wealth of materials needed to develop course units on black women; political theory, literary essays on major writers, guidelines for consciousness-raising about racism, and surveys of black women's contributions to the blues. "Important and innovative
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; fem1000; fem7000; femmes* afro-américaines; féminismes noirs; intersectionnalité; lit3220; premier cycle; périodes historiques; racisme; régions géographiques; savoirs; sexisme; systèmes d'oppressions; états-unis